(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Carpal tunnel syndrome is a commonly prevalent entrapment neuropathy characterized by median nerve compression within the carpal tunnel. The aim of this study was to compare the outcomes of transverse mini-incision and traditional mini-palm incision for carpal tunnel release. Methods: A non-randomized interventional study was done at Kurmitola General Hospital, Dhaka and US Bangla Medical College Hospital, Narayangonj between January 2019 and December 2021. Forty-two patients diagnosed with idiopathic carpal tunnel syndrome were allocated to the transverse mini-incision group (n=20) and traditional mini-palm incision group (n=22). Results: Patients operated with transverse mini-incision returned to their work significantly earlier (mean 10.3 days) than patients operated with traditional mini-palm incision (mean 18.7 days). No significant difference was found between transverse mini-incision group and traditional mini-palm incision group as determined by the McGill pain score improvement (P=0.16), the Bangla version of the Boston carpal tunnel questionnaire symptom severity score (P=0.61) and functional severity score (P=0.43). Conclusion: Transverse mini-incision is comparable to the traditional mini-palm incision in terms of pain, other symptoms, and functional outcome. However, patients in transverse mini-incision group could return earlier to work. Bangabandhu Sheikh Mujib Medical University Journal 2023;16(3): 167-171